Несколько замечаний по поводу второго тома «Мертвых душ»(Some Comments on the Second Volume of “Dead Souls”) - Egeberg, Erik (Poljarnyj vestnik, 2003)
The present article deals with the various problems that faced N. V. Gogol' working on vol. II of his great novel. Attention is paid not only to ideological and psychological matters, but also to the more complicated composition pattern which can be discerned in the five preserved chapters of "Dead Souls" II.
Keywords: Russian literature; Gogol; Dead Souls